Mapping the service recovery research landscape: A bibliometric‐based systematic review - Mir, Mahmood; Ashraf, Rohail; Syed, Tahir Abbas; Ali, Sara; Nawaz, Raheel (Psychology & marketing, 2023)
With businesses under increasing pressure to provide excellent customer service, postfailure recovery strategies have become critical for long‐term customer satisfaction and loyalty. The domain of service recovery has extensively been examined in academia; however, systematic studies that provide a consolidated overview remains scant. To this end, we provide a systematic review and synthesis of service recovery literature by conducting a bibliometric‐based cocitation analysis of 24,741 cited references from 1020 articles from across disciplines. The study identifies 10 major research clusters that represent different research streams of service recovery and explores their intellectual foundations. In addition, the research presents a conceptual framework to serve as a parsimonious guide for both practitioners and researchers. Furthermore, the study reveals a number of gaps in the existing literature and suggests promising directions for further investigation, including but not limited to: expanding methodological horizons in service recovery research, understanding service recovery mechanisms in Metaverse and synthetic environments, globalizing service recovery research, revitalizing service recovery processes in the age of artificial intelligence and robotics, investigating service recovery as an investment, and exploring service recovery in shared economies. Notably, this study serves managers, firstly, by providing them with a parsimonious structure of service recovery field that could help identify areas of improvement in their own service recovery systems and, secondly, by highlighting areas where academic knowledge base could inform industry solutions.